Adil Dalam al-Quran: Konsep, Implementasi, Dan Relevansinya Dalam Kehidupan Modern - Chaliddin Chaliddin; Munawar Khalil; Nazaruddin Nazaruddin (Siyasah Wa Qanuniyah, 2024)
Justice in Islam is a fundamental concept that is regulated in the Quran. Justice is defined as acting impartially, giving rights to the rightful, and putting everything in its place. In this context, this article aims to analyze the concept of justice in the Quran and its implications for the daily lives of Muslims. Through a qualitative approach, this article explores various verses that discuss justice and how these principles can be applied in modern society. The results show that the concept of justice in the Quran is not only theoretical, but also has practical relevance in facing the challenges of the times. Justice, both in the relationship between creatures and the Creator and between fellow human beings, is the foundation that supports the creation of a harmonious life in accordance with Islamic principles.